Komunikasi Persuasif Lembaga Dakwah MPM Al-Jihad Fisip Untad dalam Merekrut Kader Baru - Suriyani (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
This research aims to find out how the persuasive communication techniques of the MPM Al-Jihad Fisip Untad da’wah institution are used in recruiting new cadres. This research is descriptive qualitative in nature with the research base being a case study. This research uses data collection techniques through observation and interviews with sources determined based on purposive sampling techniques. The results of this research show that the MPM Al-Jihad administrators use five persuasive communication techniques, namely the association technique, integration techniques, arrangement technique, reward technique, and red-herring techniques. These techniques aim to attract the interest of Muslim students from the Faculty of Social and Political Sciences, class of 2023. However, most of the Muslim students from the Faculty of Social and Political Sciences, class of 2023, are not interested in joining. This is because the Muslim Faculty of Social and Political Sciences Untad class of 2023 students feel that the persuasive communication techniques used are not relevant to their needs